Fatores determinantes da ino vação no Instituto Nacional de Criminalística e na Diretoria Técnico-Científica da Polícia Federal - Bento, Getúlio Menezes (2013)
Few issues have been characterized by as much agree ment among organizational researchers as the importance of innovation to orga nizational competitiveness and effectiveness. The theme of innovation is as import ant as is its vast and diverse literature. But, if on one hand it recognizes the i mportance of the issue, on the other hand, it turns out that the understanding of innova tive behavior in organizations remains relatively undeveloped, especially in the p ublic sector. From the point of view of the innovation management, the question arises w hat are the organizational factors that determine the innovation capability in the organization. In this respect, the aim of this study was to identify the character istics and organizational factors driving or inhibiting the innovation process at the National Institute of Criminalistics and Technical-Scientific Directorate, considering t he organization members' perception who were involved with the development o f innovative ideas in the studied environment. For this purpose, a survey was conduct ed to assess the perception of the subjects about 15 factors relevant to innovatio n processes, postulated by researchers of the Minnesota Innovation Research Pr ogram - MIRP, University of Minnesota. The sample was composed of 62 organizati onal actors who returned the questionnaire sent to 79 experts, who were involved in the development of 42 different innovative ideas. Results indicated that ten factors (67%) induced the development of innovative processes while three fac tors (20%) inhibited these processes. Two factors had little convergence of an swers, so that results do not allow to conclude whether these factors acted foste ring or inhibiting innovation. Results confirmed the research assumption that the organizational environment provides mechanisms for fostering innovations.